Automating a Magnetic 3D Spheroid Model Technology for High-Throughput Screening - Baillargeon, Pierre (SLAS Technol, 2019)
Affordable and physiologically relevant three-dimensional cell-based assays used in high-throughput screening are on the rise in early drug discovery. These technologies have been aided by the recent adaptation of novel microplate treatments and spheroid culturing techniques. One such technology involves the use of nanoparticle (NanoShuttle-PL) labeled cells and custom magnetic drives to assist in cell aggregation to ensure rapid 3D structure formation after the cells have been dispensed into microtiter plates. Transitioning this technology from a low-throughput manual benchtop application, as previously published by our lab, into a robotically enabled format achieves orders of magnitude greater throughput but required the development of specialized support hardware. This effort included in-house development, fabrication, and testing of ancillary devices that assist robotic handing and high precision placement of microtiter plates into an incubator embedded with magnetic drives. Utilizing a “rapid prototyping” approach facilitated by cloud-based CAD software, we built the necessary components using hobby-grade 3D printers with turnaround times that rival traditional manufacturing/development practices at a substantially reduced cost. This approach culminated in a first-in-class HTS compatible 3D system in which we have coupled 3D bioprinting to a fully automated HTS robotic platform utilizing our novel magnetic incubator shelf assemblies.